LUK 24:13-35 DAN TEOLOGI SINODALITAS - Bangun, Nathanio C. Maranatha; Marmidi, F.X.; Stanislaus, Surip (LOGOS, 2024)
This study seeks to explore how the Gospel of Luke 24:13-35 embodies a theology of synodality. The theology of synodality has become a central focus in the life of the Catholic Church today, particularly since Pope Francis highlighted its importance in the third millennium. Synodality, etymologically meaning "walking together" (synodos), is based on three main pillars: communion, participation, and mission among all Church members. In this context, the passage from Luke 24:13-35, which describes the journey to Emmaus, offers rich, profound, and relevant insights to enhance and deepen the theology of synodality. This article aims to analyze this passage using both synchronic and diachronic approaches, examining the writings of the Church Fathers, Church documents, and Church history. The results of this analysis will then be engaged in dialogue with the theology of synodality to explore its relevance and potential contributions to this theological framework.